2019
DOI: 10.1109/access.2019.2901849
|View full text |Cite
|
Sign up to set email alerts
|

Improved Biogeography-Based Optimization Algorithm and Its Application to Clustering Optimization and Medical Image Segmentation

Abstract: In order to improve the optimization efficiency of the biogeography-based optimization (BBO) algorithm, an improved BBO algorithm, that is, worst opposition learning and random-scaled differential mutation BBO (WRBBO), is presented in this paper. First, BBO's mutation operator is deleted to reduce the computational complexity and a more efficient random-scaled differential mutation operator is merged into BBO's migration operator to obtain global search ability. Second, in order to balance exploration and expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…From this table, we have observed that meta-heuristic based rule miners are very competitive to the hybride metaheuristic based classification on credit score assessment and can add another dimension to the field of rule mining with a great success of classifying an unseen sample if work on it can be intensified. As a consequence, several credit scoring models make use of hybrid mining approaches to support credit approval decisions (Zhang, Wang, & Chen, 2019). Initially, parametric statistical techniques have employed for credit scoring.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…From this table, we have observed that meta-heuristic based rule miners are very competitive to the hybride metaheuristic based classification on credit score assessment and can add another dimension to the field of rule mining with a great success of classifying an unseen sample if work on it can be intensified. As a consequence, several credit scoring models make use of hybrid mining approaches to support credit approval decisions (Zhang, Wang, & Chen, 2019). Initially, parametric statistical techniques have employed for credit scoring.…”
Section: Related Workmentioning
confidence: 99%
“…In general, the selection operator is used to assess the probability of As a result, it is very often noticed that a bad model is directly influenced by a rule which is better in a local context rather than a global context. Moreover, migration and mutation operators are two imperative features that largely affect the performance and computational efficiency in BBO, which maintain both exploration and exploitation of existing approaches (Zhang et al, 2019).…”
Section: Selectionmentioning
confidence: 99%
“…In addition, the following improvements are also adopted. First, the greedy selection [24,37] replaces the elitism strategy [8]. So, on the one hand, the population is just needed to sort once at each iteration to reduce computing complex; on the other hand, the greedy selection avoids setting the elitist parameter.…”
Section: Dynamic Two-differential Perturbing Operator De Proposed Bymentioning
confidence: 99%
“…GLxBBO is an incomplete variant of ILxBBO, which is LxBBO with only the two-global-best guiding operator, without the dynamic two-differential perturbing operator and improved Laplace migration operator DLxBBO is an incomplete variant of ILxBBO, which is LxBBO with only the dynamic two-differential perturbing operator without the improved Laplace migration operator and two-global-best guiding operator OLxBBO is an incomplete variant of ILxBBO, which contains the improved Laplace migration operator without the dynamic two-differential perturbing operator and two-global-best guiding operator e experimental results are shown in Table 1 [39], BIBBO [25], BBOM [40], DEBBO [30], BLPSO [41], PRBBO [24], WRBBO [37], EMBBO [27], and BHCS [42]. ese algorithms are all BBO variants proposed in recent years, with much comparability.…”
Section: Comparison Of Ilxbbo With Its Incomplete Variantsmentioning
confidence: 99%
“…Species living in a geography that has high HSI emigrates to nearby habitats, which has low species, since this biogeography is already nearly saturated. BBO has been used for clustering in some studies [22,23]. As seen in Table 3, since BBO algorithm uses three loops, BBO runs slower than the other algorithms like PSO and GWO.…”
Section: Biogeography-based Optimizationmentioning
confidence: 99%